Structural diversity and biological importance of ABO, H, Lewis and secretor histo-blood group carbohydrates - Mattos,Luiz Carlos de (2016)
ABSTRACT ABO, H, secretor and Lewis histo-blood system genes control the expression of part of the carbohydrate repertoire present in areas of the body occupied by microorganisms. These carbohydrates, besides having great structural diversity, act as potential receptors for pathogenic and non-pathogenic microorganisms influencing susceptibility and resistance to infection and illness. Despite the knowledge of some structural variability of these carbohydrate antigens and their polymorphic levels of expression in tissue and exocrine secretions, little is known about their biological importance and potential applications in medicine. This review highlights the structural diversity, the biological importance and potential applications of ABO, H, Lewis and secretor histo-blood carbohydrates.